The right to have rights: a criminological and social analysis of abortion in Costa Rica - Villarreal Salazar, Jéssica (2025)
The article aims to make visible the issue of abortion and the social implications of criminalization in Costa Rica. The methodology used was documentary and narrative analysis based on fragments of interviews. The results show that the criminalization of abortion reinforces unequal conditions. It was observed that the body is both the vehicle for struggle and the cause. Among the most relevant conclusions, it stands out how setbacks in Human Rights have been created from the power of the State and how women’s bodies are situated as a space for emancipation.